2019
DOI: 10.1177/0004867419853882
|View full text |Cite
|
Sign up to set email alerts
|

History of abuse and neglect and their associations with mental health in rescued child labourers in Nepal

Abstract: Objectives: Little is known about rates of childhood maltreatment in low-income countries, particularly among marginalised sectors of society. Economic hardships mean that in such countries, many children and young people are exploited in the labour force and/or are trafficked, placing them at greater risk for being exposed to other forms of maltreatment. Cultural norms endorsing the use of physical and emotional acts to discipline children further exacerbate this risk. Here, we assessed the rates of childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 19 publications
(31 reference statements)
4
24
1
Order By: Relevance
“…Children's psychosocial distress includes traumas associated with separation from peers and wider kinship groups due to migration and difficulties in making social bonds, particularly for independent child labourers (ILO, 2018). This is supported in a study with young people in Nepal who had previously been child labourers and reported the impact of social stigma and disconnect with cultural norms, leading to anxiety disorders, panic attacks and social phobias (Dhakal et al, 2019).…”
Section: Situation Of Children Working In Nepalese Brick Kilnsmentioning
confidence: 73%
See 2 more Smart Citations
“…Children's psychosocial distress includes traumas associated with separation from peers and wider kinship groups due to migration and difficulties in making social bonds, particularly for independent child labourers (ILO, 2018). This is supported in a study with young people in Nepal who had previously been child labourers and reported the impact of social stigma and disconnect with cultural norms, leading to anxiety disorders, panic attacks and social phobias (Dhakal et al, 2019).…”
Section: Situation Of Children Working In Nepalese Brick Kilnsmentioning
confidence: 73%
“…Other factors that arose in the review include family dynamics, lack of choice, poor education system, peer pressure and aspirations provided by returning labourers. Several studies report that poverty is the major push factor for children's migration (Dhakal et al, 2019; Kamei, 2018; Rijal et al, 2016; Save the Children, 2019). Changes in family dynamics through events such as illness, disability, death or departure of one or both parents can drastically change a child's life and intensify risk of poverty (Guragain, Paudel, Lim, & Choonpradub, 2015).…”
Section: Seasonal In‐country Migration To Brick Kilns and Impacts On mentioning
confidence: 99%
See 1 more Smart Citation
“…In Nepal, child clubs encourage participation and support self-actualisation and agency of children to bring about change, for example, persuading their families to send them to school (Save the Children, 2016). More research on the role of life skills education for adolescents and specific mental health and counselling services for youths previously involved in child labour is needed (Dhakal et al, 2019;International Labour Organisation, 2018). There is limited research from the perspectives of children and youth on their experiences and longer term effects of education and support services, made difficult in part, by migration to various locations (Dobson, 2009; Save the Children, 2019).…”
Section: Educational Opportunitiesmentioning
confidence: 99%
“…Anxiety is a disorder that can be developed in offspring as a result of aversive life conditions. Some factors in the childhood and adolescence that predispose the development of anxiety disorders include sexual abuse [1], social isolation [2], maternal separation [3], physical abuse, emotional abuse, negligence, and exposure to partner violence [4]. In addition, children who experience multiple types of abuse can suffer exacerbate symptoms of anxiety and comorbidity with depression compared to those who are only exposed to one type of abuse [1, 5,6].…”
Section: Introductionmentioning
confidence: 99%